Mass Transfer Coefficient Study of Cherry (Muntingia calabura L.) Leaves Alkaloids Extraction Using Ethanol - Kindriari Nurma Wahyusi; Ardika Nurmawati; Yuliyatin Zaen (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
Cherry (Muntingia calabura L.) leaves have been acknowledged for their potential as a rich source of various components including alkaloid, flavonoid, tannin, saponin, triterpenes, and polyphenol. Alkaloids play diverse roles in medical science. Isolated alkaloids from plants are already widely used in traditional medicine. Obtaining alkaloids from the leaves required an extraction process using organic solvent. This study aimed to evaluate the mass transfer coefficient for the extraction of alkaloids from cherry leaves using ethanol as a solvent. Dried cherry leaves were contacted with 96% ethanol at different temperatures and contact times. The extraction temperature ranged from 60, 65, 70, 75, and 80oC while the contact time varied from 30, 60, 90, 120, and 150 minutes. The extraction process was conducted with a mixing speed of 440 rpm. With the increasing contact time and extraction temperature, there was a corresponding increase in alkaloid concentrations. The optimal extraction conditions were achieved at 75oC with an extraction time of 150 minutes, resulting in an alkaloid content of 0.6486 gr/ml. The mass transfer coefficient under these extraction process conditions was 1.7923 hour-1. These data are crucial for the design and scale-up of extractors to achieve optimal results.